Consensus development of priority outcome domains for community mental health cares by multiple stakeholders: Protocol for an online Delphi study in Japan - Takuma Shiozawa; Sosei Yamaguchi; Makoto Ogawa; Makiko Abe; Takayuki Kawaguchi; Momoka Igarashi; Naonori Yasuma; Chiyo Fujii (Wiley, 2021)
Abstract Background Treatment goals for mental illness have expanded from hospital discharge and improved functioning to employment, living alone, and personal realization. These changes in treatment goals have also influenced mental health research. Recent studies have addressed the development of core outcome sets focusing on clinical aspects of mental illness such as depression and anxiety. However, a well‐developed framework of essential outcomes for people with mental illness (service users) who live in the community is lacking. In addition, recent worldwide trends suggest more patient and public involvement and the importance of considering multiple stakeholders' views in the area of mental health research. Purpose of this study is to explore consensus on high‐priority outcome domains among multiple stakeholders in community mental healthcare fields in Japan. Methods A three‐step approach to developing an outcome list will be used. First, we developed a long list of outcomes for community mental health through a literature review, focus group interviews with key stakeholders, and online questionnaire surveys of service users and caregivers. Second, the long list was checked and revised in a pilot study. Third, the long list will be shortened to the outcome list through the Delphi methodology with participation from multiple stakeholders. Discussion Identifying important common outcome domains through collaboration with multiple stakeholders appears to contribute to the development of evidence for community mental health research in Japan. In addition, the study process itself may help promote patient and public involvement in education, practice, and research in the field of community mental health.